Effect of adding Ce on the optostructural and electrical properties of cubic CaSnO3. (4th March 2022) - Balasundaram, V.; Balasubramanian, V.; Senthil Siva Subramanian, T.; Henry, J.; Daniel, T.; Mohanraj, K.; Sivakumar, G.
Abstract: CaSnO3 and Ce doped CaSnO3 particles were synthesized by co-precipitation method. An X-ray diffraction study shows that the synthesized CaSnO3 particles belongs to orthorhombic structure and the crystalline peaks shift toward higher angle with increasing Ce concentration. The Fourier Transform Infrared Spectra witnessed the presence of Ca-O, Sn-O and Ce-O vibrations in the synthesized particles. The optical absorption is higher in the UV-region and the band gap energy is decreased from 4.3 eV to 3.2 eV. The photoluminescence spectra affirmed that the emission peak shifts toward the visible region during the incorporation of Ce. Scanning electron microscope images depicted the cubic block-like morphology with sharp edges. From the electrochemical measurements, 0.02 M Ce doped CaSnO3 electrode exhibited higher specific capacitance value of 916 F/g due to its lower charge transfer resistance value than that of 0.01 M and 0.03 M Ce doped CaSnO3 . Graphical Abstract: UF0001